Management of Strategic Resources as a Function of the Russian State - Ivanitsky, Viktor Pavlovich; Privalov, Nikolay Gennadevich (Economy of Regions, 2016)
The function of the state - the management of strategic resources - becomes relevant on the threshold of the post-market economy and global depletion of mineral resources. The economic and political situation in the world is aggravated by the crisis of state system as the institution of management. In the article, the approach to the definition of the strategic resources of the state is presented. The examples of measures taken by the modern states to overcome this crisis are given. The thesis that the possession of strategic resources at the crisis moments of history becomes the essential tool in the political, economic and military confrontation of powers is proved. The question of the politicization of the market of mineral resources is brought up, and the current examples of such phenomenon are given. In the article, the arguments that the management of strategic resources in the near future will become the monopoly of the state are adduced. This implies a sharp weakening of the private part in this domain/ sphere as it is in the interest of survival of the state and populace. The problem of the global depletion of mineral resources which influences the management of strategic resources is considered. The statistical analysis of mineral wealth in Russia and in the world is provided. Institutional (cultural) arguments for the sharp weakening of market tools in the management of strategic resources are analysed. The genesis of the study of the mentality of Slavs, Muslims and Hindus is given, according to which the only private possession of natural resources would be impossible and inadmissible. In the article, the various options of the growth of the state influence on the strategic resources in the new economic policy developed in Russia are offered.